(3faMGJ GdYfHQ HaVdGA hCYjGf Gdjef aj GdbQf GdKGfi YTQs - (3EHQGgje Hf YHO Gddg Hf ESeGYjd GdMhJi GdMSjfs; (3EHQGgje Hf YHO Gddg Hf ESeGYjd GdMeRj GdMSjfj Gdjefj,J (B1223 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO ajbhd GdabjQ GdMhJi GdMSjf bO LYdJ eDdakG Ydi JQLeI TjNfG YHO GdbGOQ Hf CMeO hSejJg HbQI GdfhGXQ de jcf JQJjHge Sgd GdeCNP s
(3BNQgG (B:s
(3JQGLeg GdQMef UahI ef CJi HeYLRI cGdTeS bGeJ Edi GdMTQ gfG BNQ GdLRA GdChd s
(3cJHJ HNWhW eNJdaI HYVgG deMeO Hf CMeO Hf YHO Gddg eQJH Ydi MQha GdeYLes
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B50s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs